Pengembangan Skala Alienasi Siswa Sekolah Menengah - Laurens Kaluge; Sumiyarno Sumiyarno (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was aimed at developing a battery of high school student alienation called SASSM (Skala Alienasi Siswa Sekolah Menengah). It refered to pooling items, searching the dimensions, the characteristics, and the reliability of the dimensions. The data were collected through discussion, literature review, Q-sorting, and questionnaire. The 100 pooled items were identified. The exploratory factor analysis extracted 7 dimensions consisted of 47 items. By using confirmatory factor analysis, the same dimensions and items were confirmed. These dimensions were task powerlessness, social powerlessness, meaninglessness, self-estrangement, value isolation, lovelessness, and joylessness.